A method for preparing a surface-coated manganese dioxide negative electrode material
By co-precipitation and coating manganese dioxide with copper salt, molybdate and folic acid, and calcining at high temperature to form a cladding layer, the conductivity and cycle stability of manganese dioxide in lithium-ion batteries is solved, and the problems of manganese dioxide are significantly improved. Its electrochemical properties are achieved.
Patent Information
- Application Number
- CN202211106461.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-12
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-09-12
AI Technical Summary
The existing manganese dioxide anode materials in lithium-ion batteries have poor rate performance and cycle stability due to low inherent conductivity and large volume changes, making it difficult to meet the demand for high energy density.
Manganese dioxide is coated by co-precipitation of metal copper salts, molybdate and folic acid, and a molybdenum oxide, elemental copper and nitrogen doped carbon coating is formed during high-temperature calcination.
Improved the conductivity and cycling performance of manganese dioxide. The capacity can still be maintained at 400 mAh g-1 or above after 50 weeks of cycling at 200mA g-1, while the uncovered manganese dioxide can only maintain 200 under the same conditions. mAh g-1.
Smart Images

Figure CN115385381B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery material preparation, and in particular to a method for preparing a surface-coated manganese dioxide negative electrode material. Background Art
[0002] In recent years, the rapid consumption of fossil energy and environmental pollution have forced people to conduct extensive research on the development of clean and renewable energy. Electrochemical energy is widely regarded as a promising energy source due to its sustainability and environmental friendliness. In electrochemical energy storage systems, electrode materials are the main factors affecting the performance of lithium batteries. However, the theoretical capacity of commercial graphite is limited to only 372 mAh g -1 , which is far from meeting the growing demand for high energy density in future batteries. Transition metal oxide manganese dioxide has the advantages of high energy density, low cost, green environmental protection, and high abundance, and is considered to be a very promising negative electrode material for lithium-ion batteries. However, they face serious challenges, such as low intrinsic conductivity, and poor rate performance and cycle stability due to large volume changes during lithiation / delithiation.
[0003] In order to overcome these shortcomings, various strategies have been proposed. One strategy is to prepare various nano-manganese dioxide, such as nanorods (CN112635706A, CN105869915A), nanospheres (Current Applied Physics, 2019, 19 (6), 768), porous nanostructures (Electrochemistry Communications, 2010, 12 (11), 1520-1523), etc. The nanostructure can not only provide a larger electrode-electrolyte contact area, but also alleviate the negative impact of the volume change of the material during lithium insertion / extraction, thereby improving the specific capacity and cycle performance of the electrode. Another strategy is to combine manganese dioxide with various carbon materials to improve the conductivity of lithium-ion battery negative electrode materials, such as graphene / MnO2 (CN112635706B), manganese dioxide / carbon nanotubes (CN109346734A), etc. However, the synthesis process of nano-scale methods is usually complicated, and some also require synthesis templates and carbon material composite processes. The conductive carbon used is usually expensive, and it is difficult to control the structure of the product. Therefore, obtaining a modified manganese dioxide negative electrode material with long cycle life and high capacity through a simple and easy process design has become the key to lithium-ion battery negative electrode materials. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a method for preparing a surface-coated manganese dioxide negative electrode material.
[0005] To achieve the above object, the technical solution of the present invention is as follows: A method for preparing a surface-coated manganese dioxide negative electrode material comprises the following steps:
[0006] Step 1: Add manganese sulfate and potassium permanganate into deionized water, stir mechanically until completely dissolved, and then transfer into a polytetrafluoroethylene-lined autoclave for hydrothermal reaction. After the reaction is completed, collect the product, centrifuge, wash and dry to obtain the product manganese dioxide.
[0007] Step 2: Copper acetate, (NH4)6Mo7O 24 •4H2O, the product MnO2 obtained in the above steps is dispersed in deionized water with mechanical stirring to obtain liquid A.
[0008] Step 3: Disperse folic acid in anhydrous ethanol and obtain liquid B by mechanical stirring.
[0009] Step 4: Mix solution A and solution B, continue to stir evenly, obtain a dark green precipitate, centrifuge and wash, and obtain a manganese dioxide-coated precursor.
[0010] Step 5: calcining the manganese dioxide-coated precursor obtained in step 4 in an argon atmosphere in a tubular furnace to obtain surface-coated manganese dioxide.
[0011] Preferably, in step 1, the molar ratio of manganese sulfate to potassium permanganate is 1:3-6.
[0012] Preferably, in step 1, the hydrothermal reaction temperature is 140-180° C., and the reaction time is 2-8 hours.
[0013] Preferably, in step 2, the molar ratio of cupric acetate to ammonium molybdate tetrahydrate is 3 to 5:1.
[0014] Preferably, in step 2, the molar ratio of copper acetate to manganese dioxide is 1:1-3.
[0015] Preferably, in step 2, the mechanical stirring speed is 400 rpm and the stirring time is 1 to 3 hours.
[0016] Preferably, in step 3, the molar ratio of the added folic acid to the coated manganese dioxide is 1:2-4.
[0017] Preferably, in step 3, the mechanical stirring speed is 400 rpm and the stirring time is 1 to 3 hours.
[0018] Preferably, in step 4, the mechanical stirring speed is 400 rpm and the stirring time is 10 to 24 hours.
[0019] Preferably, in step 4, the stirring temperature is 20-30°C.
[0020] Preferably, in step 5, the calcination temperature is 600-800°C.
[0021] Preferably, in step 5, the calcination time is 2 to 8 hours.
[0022] Beneficial effects:
[0023] The present invention reports a method for preparing a surface-coated manganese dioxide negative electrode material. The present invention uses a method of co-precipitation of a metal copper salt, molybdate and folic acid to coat manganese dioxide, and produces molybdenum oxide, elemental copper and nitrogen-doped carbon coating layers during high-temperature calcination. Nitrogen-containing folic acid is used for the first time, and nitrogen-doped carbon is obtained by calcination in one step. At the same time, the reducing gas decomposed by the organic acid reduces the copper ions to elemental copper, further enhancing the conductivity of manganese dioxide. Figure 3 The impedance spectrum confirms this conclusion. The three components in the coating layer work together to effectively improve the cycle performance of manganese dioxide, 200mA g -1 The capacity can still be maintained at 400 mAh g after 50 cycles. -1 The capacity of the uncoated manganese dioxide was less than 200 mAh g after 50 cycles. -1 ,like Figure 2 shown. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.
[0025] Figure 1 1 is an XRD diagram of the surface-coated manganese dioxide negative electrode material prepared in Example 1 of the present invention and Comparative Example 1;
[0026] Figure 2 Graphs showing the charge and discharge cycle performance of some typical embodiments of the present invention as negative electrode materials for lithium-ion batteries;
[0027] Figure 3 1 is an impedance diagram of the surface-coated manganese dioxide negative electrode material prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] Example 1
[0030] This embodiment provides a method for preparing a surface-coated manganese dioxide negative electrode material, which specifically includes the following steps:
[0031] Step 1, weigh 0.01 mol manganese sulfate and 0.03 mol potassium permanganate, add them into 250 ml deionized water, stir mechanically to completely dissolve, then transfer all the solution into a polytetrafluoroethylene-lined autoclave, hydrothermally react at 140° C. for 2 hours, collect the product after the reaction is completed, centrifuge, wash and dry to obtain the product manganese dioxide.
[0032] Step 2: 0.003 mol of copper acetate, 0.001 mol of (NH4)6Mo7O 24 •4H2O was dissolved in 200ml of deionized water, and then 0.003 mol of MnO2 obtained in the above step was added to the solution, and mechanically stirred for 1h to obtain liquid A.
[0033] Step 3: Disperse 0.0015 mol of folic acid in 200 ml of anhydrous ethanol and stir mechanically for 1 hour to obtain liquid B.
[0034] Step 4: Mix solution A and solution B, stir at 20° C. and 400 rpm for 10 h to obtain a dark green precipitate, and centrifuge and wash to obtain a manganese dioxide-coated precursor.
[0035] Step 5: calcining the manganese dioxide-coated precursor obtained in step 4 at 600° C. in an argon atmosphere in a tubular furnace for 2 h to obtain surface-coated manganese dioxide.
[0036] The XRD pattern of the product prepared in this example is as follows Figure 1 As shown in the figure, it can be seen that the XRD diffraction peak of the coated manganese dioxide material is consistent with the diffraction peak of the standard spectrum of manganese dioxide, indicating that the prepared product is manganese dioxide, and the coating layer material has no diffraction peak, which may be related to the small thickness of the coating layer and the low content of the material. The manganese dioxide material synthesized in this embodiment is used as a negative electrode material for lithium-ion batteries, and its charge and discharge cycle performance is as follows Figure 2 As shown in the figure, the cycle performance is greatly improved after coating, 200mA g -1 At this current, after 50 cycles, the discharge capacity is still 518.1 mAh g -1 The electrochemical impedance spectrum of the synthetic material in this example is as follows Figure 3 As shown, the impedance results show that the coated material has a smaller resistance and is more conducive to the insertion and extraction of lithium ions, thereby improving its electrochemical performance.
[0037] Example 2
[0038] This embodiment provides a method for preparing a surface-coated manganese dioxide negative electrode material, which specifically includes the following steps:
[0039] Step 1, weigh 0.01 mol manganese sulfate and 0.04 mol potassium permanganate, add them into 250 ml deionized water, stir mechanically to completely dissolve, then transfer all the solution into a polytetrafluoroethylene-lined autoclave, hydrothermally react at 160° C. for 5 hours, collect the product after the reaction is completed, centrifuge, wash and dry to obtain the product manganese dioxide.
[0040] Step 2: 0.004 mol of copper acetate, 0.001 mol of (NH4)6Mo7O 24 •4H2O was dissolved in 200ml of deionized water, and then 0.008 mol of MnO2 obtained in the above step was added to the solution, and mechanically stirred for 2h to obtain liquid A.
[0041] Step 3: Disperse 0.0027 mol of folic acid in 200 ml of anhydrous ethanol and stir mechanically for 2 h to obtain liquid B.
[0042] Step 4: Mix solution A and solution B, stir at 25° C. and 400 rpm for 17 h to obtain a dark green precipitate, and centrifuge and wash to obtain a manganese dioxide-coated precursor.
[0043] Step 5: calcine the manganese dioxide-coated precursor obtained in step 4 at 700° C. in an argon atmosphere in a tubular furnace for 5 hours to obtain surface-coated manganese dioxide.
[0044] The manganese dioxide material synthesized in this embodiment is used as a negative electrode material for lithium-ion batteries, and its charge and discharge cycle performance is as follows: Figure 2 As shown in the figure, the cycle performance is greatly improved after coating, 200mA g -1 At this current, after 50 cycles, the discharge capacity is still 401.9 mAh g -1 .
[0045] Example 3
[0046] This embodiment provides a method for preparing a surface-coated manganese dioxide negative electrode material, which specifically includes the following steps:
[0047] Step 1, weigh 0.01 mol manganese sulfate and 0.06 mol potassium permanganate, add them into 250 ml deionized water, stir mechanically to completely dissolve, then transfer all the solution into a polytetrafluoroethylene-lined autoclave, hydrothermally react at 180° C. for 8 hours, collect the product after the reaction is completed, centrifuge, wash and dry to obtain the product manganese dioxide.
[0048] Step 2: 0.005 mol of copper acetate, 0.001 mol of (NH4)6Mo7O 24 •4H2O was dissolved in 200ml of deionized water, and then 0.015 mol of MnO2 obtained in the above step was added to the solution, and mechanically stirred for 3h to obtain liquid A.
[0049] Step 3: Disperse 0.0038 mol of folic acid in 200 ml of anhydrous ethanol and stir mechanically for 3 hours to obtain liquid B.
[0050] Step 4: Mix solution A and solution B, stir at 30° C. and 400 rpm for 24 h to obtain a dark green precipitate, and centrifuge and wash to obtain a manganese dioxide-coated precursor.
[0051] Step 5: calcining the manganese dioxide-coated precursor obtained in step 4 at 800° C. in an argon atmosphere in a tubular furnace for 8 h to obtain surface-coated manganese dioxide.
[0052] The manganese dioxide material synthesized in this embodiment is used as a negative electrode material for lithium-ion batteries, and its charge and discharge cycle performance is as follows: Figure 2 As shown in the figure, the cycle performance is greatly improved after coating, 200mA g -1 At this current, after 50 cycles, the discharge capacity is still 410.6 mAh g -1 .
[0053] Example 4
[0054] This embodiment provides a method for preparing a surface-coated manganese dioxide negative electrode material, which specifically includes the following steps:
[0055] Step 1, weigh 0.01 mol manganese sulfate and 0.05 mol potassium permanganate, add them into 250 ml deionized water, stir mechanically to completely dissolve, then transfer all the solution into a polytetrafluoroethylene-lined autoclave, hydrothermally react at 170° C. for 4 hours, collect the product after the reaction is completed, centrifuge, wash and dry to obtain the product manganese dioxide.
[0056] Step 2: 0.005 mol of copper acetate, 0.001 mol of (NH4)6Mo7O 24 •4H2O was dissolved in 200ml of deionized water, and then 0.006 mol of MnO2 obtained in the above step was added to the solution, and mechanically stirred at 400 rpm for 2h to obtain liquid A.
[0057] Step 3: Disperse 0.003 mol of folic acid in 200 ml of anhydrous ethanol and stir mechanically for 2 h to obtain liquid B.
[0058] Step 4: Mix solution A and solution B, stir at 25° C. and 400 rpm for 14 h to obtain a dark green precipitate, and centrifuge and wash to obtain a manganese dioxide-coated precursor.
[0059] Step 5: calcining the manganese dioxide-coated precursor obtained in step 4 at 700° C. in an argon atmosphere in a tubular furnace for 3 h to obtain surface-coated manganese dioxide.
[0060] The manganese dioxide material synthesized in this example is used as a negative electrode material for lithium-ion batteries, and its charge-discharge cycle performance is greatly improved, 200mA g -1 At this current, after 50 cycles, the discharge capacity is still 423.4 mAh g -1 .
[0061] Example 5
[0062] This embodiment provides a method for preparing a surface-coated manganese dioxide negative electrode material, which specifically includes the following steps:
[0063] Step 1, weigh 0.01 mol manganese sulfate and 0.04 mol potassium permanganate, add them into 250 ml deionized water, stir mechanically to completely dissolve, then transfer all the solution into a polytetrafluoroethylene-lined autoclave, hydrothermally react at 150° C. for 6 hours, collect the product after the reaction is completed, centrifuge, wash and dry to obtain the product manganese dioxide.
[0064] Step 2: 0.004 mol of copper acetate, 0.001 mol of (NH4)6Mo7O 24 •4H2O was dissolved in 200ml of deionized water, and then 0.012 mol of MnO2 obtained in the above step was added to the solution, and mechanically stirred for 3h to obtain liquid A.
[0065] Step 3: Disperse 0.004 mol of folic acid in 200 ml of anhydrous ethanol and stir mechanically for 2 h to obtain liquid B.
[0066] Step 4: Mix solution A and solution B, stir at 30° C. and 400 rpm for 16 h to obtain a dark green precipitate, and centrifuge and wash to obtain a manganese dioxide-coated precursor.
[0067] Step 5: calcining the manganese dioxide-coated precursor obtained in step 4 at 800° C. in an argon atmosphere in a tubular furnace for 2 h to obtain surface-coated manganese dioxide.
[0068] The manganese dioxide material synthesized in this example is used as a negative electrode material for lithium-ion batteries, and its charge-discharge cycle performance is greatly improved, 200mA g -1 At this current, after 50 cycles, the discharge capacity is still 457.3 mAh g -1 .
[0069] Example 6
[0070] This embodiment provides a method for preparing a surface-coated manganese dioxide negative electrode material, which specifically includes the following steps:
[0071] Step 1, weigh 0.01 mol manganese sulfate and 0.03 mol potassium permanganate, add them into 250 ml deionized water, stir mechanically to completely dissolve, then transfer all the solution into a polytetrafluoroethylene-lined autoclave, hydrothermally react at 180° C. for 2 hours, collect the product after the reaction is completed, centrifuge, wash and dry to obtain the product manganese dioxide.
[0072] Step 2: 0.004 mol of copper acetate, 0.001 mol of (NH4)6Mo7O 24 •4H2O was dissolved in 200 ml of deionized water, and then 0.004 mol of MnO2 obtained in the above step was added to the solution, and mechanically stirred for 3 h to obtain liquid A.
[0073] Step 3: Disperse 0.002 mol of folic acid in 200 ml of anhydrous ethanol and stir mechanically for 3 h to obtain liquid B.
[0074] Step 4: Mix solution A and solution B, stir at 20°C and 400 rpm for 20 h to obtain a dark green precipitate, centrifuge and wash to obtain a manganese dioxide-coated precursor.
[0075] Step 5: calcining the manganese dioxide-coated precursor obtained in step 4 at 600° C. in an argon atmosphere in a tubular furnace for 8 h to obtain surface-coated manganese dioxide.
[0076] The manganese dioxide material synthesized in this example is used as a negative electrode material for lithium-ion batteries, and its charge-discharge cycle performance is greatly improved, 200mA g -1 At this current, after 50 cycles, the discharge capacity is still 430.8 mAh g -1 .
[0077] Comparative Example 1
[0078] Weigh 0.01 mol of manganese sulfate and 0.03 mol of potassium permanganate and add them into 250 ml of deionized water. Stir mechanically until completely dissolved. Then transfer all the solution into a polytetrafluoroethylene-lined autoclave and perform hydrothermal reaction at 140°C for 2 hours. After the reaction is completed, collect the product, centrifuge, wash and dry to obtain the product manganese dioxide.
[0079] The XRD pattern of the product prepared in this example is as follows Figure 1 As shown in the figure, it can be seen that the XRD diffraction peak of the uncoated manganese dioxide material is consistent with the diffraction peak of the standard spectrum of manganese dioxide, indicating that the prepared product is manganese dioxide. The manganese dioxide material synthesized in this embodiment is used as a negative electrode material for lithium ion batteries, and its charge and discharge cycle performance is as follows Figure 2 As shown in the figure, the uncoated material is -1 At this current, after 50 cycles, the discharge capacity is only 181.1 mAh g -1The electrochemical impedance spectrum of the synthetic material in this example is as follows Figure 3 As shown, the impedance results show that the uncoated material has a larger resistance, which is not conducive to the insertion and extraction of lithium ions, thus resulting in a decrease in its electrochemical performance.
[0080] Comparative Example 2
[0081] This embodiment provides a method for preparing a surface-coated manganese dioxide negative electrode material, which specifically includes the following steps:
[0082] Weigh 0.01 mol of manganese sulfate and 0.04 mol of potassium permanganate, add them into 250 mL of deionized water, stir mechanically to completely dissolve, then transfer all the solution into a polytetrafluoroethylene-lined autoclave, and perform hydrothermal reaction at 160° C. for 5 h. After the reaction is completed, collect the product, centrifuge, wash and dry to obtain the product manganese dioxide.
[0083] The manganese dioxide material synthesized in this example is used as a negative electrode material for lithium-ion batteries. Its charge and discharge cycle performance is similar to that of comparative example 1, 200mA g -1 At this current, after 50 cycles, the discharge capacity is only 176.4 mAh g -1 .
[0084] Comparative Example 3
[0085] Weigh 0.01 mol of manganese sulfate and 0.06 mol of potassium permanganate and add them into 250 ml of deionized water. Stir mechanically to completely dissolve. Then transfer all the solution into a polytetrafluoroethylene-lined autoclave and perform hydrothermal reaction at 180°C for 8 hours. After the reaction is completed, collect the product, centrifuge, wash and dry to obtain the product manganese dioxide.
[0086] The manganese dioxide material synthesized in this example is used as a negative electrode material for lithium-ion batteries. Its charge and discharge cycle performance is similar to that of comparative example 1, 200mA g -1 At this current, after 50 cycles, the discharge capacity is only 171.3 mAh g -1 .
[0087] It can be seen from Examples 1 to 6 and Comparative Examples 1-3 that the coated manganese dioxide composite material prepared by co-coating manganese dioxide with nitrogen-rich carbon source folic acid, copper salt and molybdate and further calcining has a reduced charge transfer resistance, a fast lithium ion transfer rate and improved cycle performance. The XRD comparison of Example 1 and Comparative Example 1 shows that the coating does not change the structure of the material, but the cycle performance is greatly improved. The coated material has a specific capacity of more than 400 mAh g after 50 cycles. -1 , while the specific capacity of the uncoated manganese dioxide electrode material under the same conditions is less than 200 mAh g -1This may be related to the composition of the special coating layer in this experiment.
Claims
1. A method for preparing a surface-coated manganese dioxide negative electrode material, characterized in that: The following steps are involved: Step 1, adding manganese sulfate and potassium permanganate into deionized water, mechanically stirring until completely dissolved, and then transferring into a polytetrafluoroethylene-lined autoclave for hydrothermal reaction. After the reaction is completed, the product is collected, centrifuged, washed and dried to obtain the product manganese dioxide; Step 2: Copper acetate, (NH4)6Mo7O 24 •4H2O, the product MnO2 obtained in the above steps is dispersed in deionized water with mechanical stirring to obtain liquid A; Step 3, dispersing folic acid in anhydrous ethanol, and mechanically stirring to obtain liquid B; Step 4, mixing solution A and solution B, continuing to stir evenly to obtain a dark green precipitate, centrifuging and washing to obtain a manganese dioxide-coated precursor; Step 5, calcining the manganese dioxide-coated precursor obtained in step 4 in an argon atmosphere in a tube furnace to obtain surface-coated manganese dioxide; In the step 2, the molar ratio of copper acetate to ammonium molybdate tetrahydrate is 3 to 5:1; In the step 2, the molar ratio of copper acetate to manganese dioxide is 1:1-3; In the step 3, the molar ratio of the added folic acid to the coated manganese dioxide is 1:2-4.
2. The method for preparing the surface-coated manganese dioxide negative electrode material according to claim 1, characterized in that: The molar ratio of manganese sulfate to potassium permanganate in step 1 is 1:3-6.
3. The method for preparing the surface-coated manganese dioxide negative electrode material according to claim 1, characterized in that: In step 1, the hydrothermal reaction temperature is 140-180° C., and the reaction time is 2-8 hours.
4. The method for preparing the surface-coated manganese dioxide negative electrode material according to claim 1, characterized in that: In step 2, the mechanical stirring speed is 400 rpm, and the stirring time is 1 to 3 hours.
5. The method for preparing the surface-coated manganese dioxide negative electrode material according to claim 1, characterized in that: In step 3, the mechanical stirring speed is 400 rpm, and the stirring time is 1 to 3 hours.
6. The method for preparing the surface-coated manganese dioxide negative electrode material according to claim 1, characterized in that: In step 4, the mechanical stirring speed is 400 rpm, the stirring time is 10 to 24 hours, and the stirring temperature is 20 to 30°C.
7. The method for preparing the surface-coated manganese dioxide negative electrode material according to claim 1, characterized in that: In step 5, the calcination temperature is 600-800° C., and the calcination time is 2-8 hours.
Citation Information
Patent Citations
Manganese dioxide nano-rod composite electrode and preparation method and application thereof
CN105869915A
Preparation method of manganese dioxide / carbon nanotube complex fuel cell cathode oxygen reduction catalyst
CN109346734A
Preparation method of graphene-manganese dioxide nanorod-shaped negative electrode material
CN112635706A
Preparation method of graphene-manganese dioxide nanorod anode material
CN112635706B
Preparation method of aqueous sodium ion battery cathode composite material
CN107732180A
Cited By
Lithium ion battery and preparation method thereof
CN121416627A
A lithium-ion battery and its preparation method
CN121416627B